The effect of iron balance on platelet counts in blood donors. Issue 2 (29th November 2016) - Eder, Anne F.; Yau, Yu Ying; West, Kamille
Abstract : BACKGROUND: Thrombocytosis (or, less commonly, thrombocytopenia) is associated with iron‐deficiency anemia and resolves with iron therapy. Many volunteer blood donors have low iron stores, with or without anemia. Iron balance could affect platelet counts in blood donors. STUDY DESIGN AND METHODS: Whole blood donors deferred for finger‐stick hemoglobin levels less than 12.5 g/dL were evaluated by complete blood count and serum iron panel before and after oral iron treatment. Group assignment for iron depletion was based on serum ferritin cutoffs of less than 20 µg/L for women and less than 30 µg/L for men or was based on changes in serum ferritin levels after iron replacement. RESULTS: Among 1273 Hb‐deferred whole blood donors, 55% (619 of 1128) of the women and 70% (102 of 145) of the men were iron depleted. Iron‐depleted donors had higher platelet counts compared with donors who had normal ferritin levels (women: 286 vs. 268 × 10 3 /µL; p < 0.0001; men: 246 vs. 222 × 10 3 /µL; p = 0.0454). Only 4.4% of iron‐depleted donors had thrombocytosis (> 400 × 10 3 /µL) compared with 2.0% of donors who had normal ferritin levels (p = 0.017). Iron replacement decreased platelet counts in iron‐depleted female donors (mean, −19, 800/µL; interquartile range, 8000 to −45, 000/μL), but not in donors who had normal or stable ferritin levels. The same trends were observed in male donors. CONCLUSION: Iron‐depleted donors had higher platelet counts than donors who had adequate iron stores. Oral iron replacement decreased platelet counts on average by about 20, 000/µL in iron‐depleted donors but had no effect on platelet counts in donors who had normal or stable ferritin levels.